Anti-neuroinflammatory and antioxidant phenols from mulberry fruit (Morus alba L.). (May 2020) - Xu, Xue; Huang, Yuying; Xu, Jingwen; He, Xiangjiu; Wang, Yihai
Graphical abstract: Highlights: Phytochemicals of mulberry fruit were conducted. Three novels and forty-seven known compounds were isolated from mulberry fruit. Some phenols showed potent anti-neuroinflammatory and antioxidant activities. Mulberry fruit could serve as a healthy product for neuroinflammatory related diseases. Abstract: Mulberry ( Morus alba L.) fruit is a delicious, fleshy, succulent berry, which is served as a famous fruit in many countries and as traditional herb in China. In our current study, three new (1, 44, 47 ) and forty-seven known compounds were isolated and identified from mulberry fruit. Anti-neuroinflammatory, antioxidant and antidiabetic activities of these compounds were evaluated in vitro . Compound 7 significantly inhibited nitric oxide (NO) production induced by lipopolysaccharides (LPS) in microglia cells (BV-2) with the IC50 value of 10.09 ± 0.51 μM. Compounds 1, 5, 7, and 14 dose-dependently reduced the expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2). Simultaneously, they could block LPS-induced nuclear translocation of nuclear factor- κ B (NF- κ B). Moreover, phenols from mulberry fruit displayed evidently antioxidant and antidiabetic activities. These results suggested that reasonable consumption of mulberry might assist people to prevent and reduce the occurrence of neuroinflammatory and oxidative related diseases.